(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2010)
The present investigation constitutes the first imposex report in Ecuador and Pacific South American coast for species Thais kiosquiformis and Thais biserialis. In addition this study included the species Thais brevidentata (Mollusca: Gasteropoda: Muricidae). The monitoring was accomplished in merchant and fishing ports and beaches of the Ecuador coast line, indicating the imposex presence in twelve of fourteen sampled localities. T. kiosquiformis was the only species observed in the estuarine environments inside the Gulf of Guayaquil. This species show, in all the collected females, high values of RPLI’s (40,7 %) and VDSI (Degree V) in comparison with T. brevidentata (2,8 % and Degree I) and T. biserialis (26,1 % and Degree the III) that appeared in the coastal oceanic waters. T. kiosquiformis was most sensitive species for estuarine areas than T. biserialis. In other hand T. biserialis was a good organotin pollution bioindicator for marine coastal waters. For the future studies recommends to increase the species number of gasteropods to monitoring in Ecuador coastal waters and to realize experimental studies to laboratory scale to determine the sensibility of the organisms to the tributyltin (TBT).